Brexpiprazole as a new approach of treatment in somatization disorder. (2022) - Chiappini, Stefania; Mosca, Alessio; Martinotti, Giovanni; Di Carlo, Francesco; Miuli, Andrea; Dattoli, Luigi; Pettorruso, Mauro; Di Giannantonio, Massimo
Abstract: Introduction: Somatic symptom disorder (SSD) is a mental disorder that involves one or more physical symptoms (e.g. palpitations, dizziness, diarrhoea, limb weakness, pain, and pseudo neurological symptoms) accompanied by one or more thoughts, feelings, and/or behaviours related to the somatic symptom(s) resulting in significant distress and/or dysfunction lasting for more than 6 months. At now the SSD can be refractory to psychiatric intervention including antidepressants, antiepileptics, and antipsychotics as well as the effectiveness of many of these treatments is limited. The objective of this study was to report the effectiveness of a third-generation antipsychotic drug brexpiprazole for treatment of a case of SSD together with the serotonin selective reuptake inhibitor (SSRI) fluvoxamine. Methods: A single case study of a 59-year-old female with SSD was here performed. Findings: After 4 weeks of treatment brexpiprazole, together with lamotrigine and fluvoxamine, was here effective in decreasing both depressive and anxiety symptoms, normalising previous unusual thought contents and of related behaviours. The patient reported an overall good response and started to function again in important domains of life. No adverse events occurred. Conclusion: To our knowledge, this is the first case showing Brexpiprazole effective for the treatment of a case of SSD as add-on to other drugs.